2018
DOI: 10.1186/s12955-018-0936-5
|View full text |Cite
|
Sign up to set email alerts
|

Health promoting lifestyles and influencing factors among empty nesters and non-empty nesters in Taiyuan, China: a cross-sectional study

Abstract: BackgroundIn China, the problems of population aging and empty nesting have become important issues which will affect the social stability and economic development. The aim of this study was to explore the health promoting lifestyles and influencing factors among empty nesters and compare with non-empty nesters to find out their differences, so as to provide a scientific evidence for people to formulate health management strategies for elderly.MethodsA cross-sectional survey which used a stratified random clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 16 publications
(20 reference statements)
1
33
0
Order By: Relevance
“…Furthermore, Zhu and Walker (2019) did not take empty-nest status and multi (morbidity) into account. These factors may significantly influence older adults' social participation ( Galenkamp & Deeg, 2016 ; Zhang et al, 2018 ) and deserve careful consideration, as they may introduce bias into the observed association between income and social participation. The present study demonstrated that income has a critical effect on the social engagement of older adults in a highly collectivistic culture over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Zhu and Walker (2019) did not take empty-nest status and multi (morbidity) into account. These factors may significantly influence older adults' social participation ( Galenkamp & Deeg, 2016 ; Zhang et al, 2018 ) and deserve careful consideration, as they may introduce bias into the observed association between income and social participation. The present study demonstrated that income has a critical effect on the social engagement of older adults in a highly collectivistic culture over time.…”
Section: Discussionmentioning
confidence: 99%
“…This inequal development has contributed to Chinese adult children's movement away from their natal areas (i.e., villages, townships, and cities), leaving their aging parents as “empty nesters” at home ( Fang et al, 2015 ; Zhang & Zhang, 2017 ). Research has shown, however, that Chinese empty-nester older adults are more socially active than are their non–empty-nester peers ( Zhang et al, 2018 ). A possible explanation is the traditional Chinese cultural expectation that older people spend time with their families at home ( Rochelle & Shardlow, 2012 ), such as by taking care of young children, before taking part in social (e.g., community) activities outside of the family sphere ( Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2011 China Health and Retirement Longitudinal Study (CHARLS) also reported that approximately 40% of older adults had depressive symptoms [14]. China is facing a rapidly aging society; the proportion of elderly has grown from 13.3% [15] to 17.9% [16] of the population between 2010 and 2018. Thus, there is a corresponding growth in the number of older people displaying depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In simplest terms, self-management describes what a person does to manage his/her disease 21 . A crosssectional study 4 found that empty nesters' awareness of self-health management is weak. Since empty nesters do not want their children to worry, they usually hide their illness and do not care about their health.…”
Section: Discussionmentioning
confidence: 99%